Ismaili Literature: A Bibliography of Sources and Studies by Farhad Daftary (London and New York: I.B. Tauris Publishers, in association with The Institute of Ismaili Studies (London), 2004. 469 pages.) (American Journal of Islam and Society, 2005)
This compilation of Ismaili literature is the result of over thirty years ofresearch, put together by one of the world’s leading experts on Ismailithought and history. Previous attempts to take account of Ismaili literaturehave been carried out by such noteworthy scholars as W. Ivanow and I.Poonawala. But as the author notes, their compilations were essentially inventories of manuscripts, whereas the present bibliography is solely concernedwith those materials, both primary sources and secondary studies,which have been published.This bibliography contains an important survey of medieval and contemporarydevelopments in Ismaili studies. Particular attention is paid to theearly polemical assaults (and many outright fabrications) to which theIsmaili image collectively fell victim and which caused numerous misunderstandingsconcerning key Ismaili doctrines. Particularly noteworthy in thisregard is the Ismaili “black legend” that surreptitiously came to the fore bythe tenth century CE (see p. 87). This image, which severely distorted Ismailiteachings with regard to both its faith and practice, resulted in increasedIsmaili polemics and hostilities. In addition, this image also suffereddefamation from outside the house of Islam, for distortions spread by theCrusaders and other European travelers resulted in a slew of embellishedtales – the “Assassin legends.” ...